Comparing Outcomes of Single-Incision Laparoscopic Herniorrhaphy in Newborns and Infants - Tsung-Jung Tsai; Ching-Min Lin; I Nok Cheang; Yao-Jen Hsu; Chin-Hun Wei; Tai-Wai Chin; Chin-Yen Wu; Wen-Yuan Chang; Yu-Wei Fu (Diagnostics, 2023)
Background: As surgical techniques progress, laparoscopic herniorrhaphy is now performed more often in premature babies. The aim of this study was to analyze the outcomes of newborns and infants who underwent single-incision laparoscopic herniorrhaphy (SILH) at our center. Methods: We retrospectively reviewed patients younger than 12 months old who received SILH at our department from 2016 to 2020. SILH involved a 5 mm 30-degree scope and 3 mm instruments with a 3-0 Silk purse-string intracorporeal suture for closure of the internal ring. At the time of surgery, Group 1 newborns, whose corrected age was 2 months and below, were compared to the Group 2 infants, whose age was above 2 months. We assessed the patients’ characteristics, anesthesia, surgical data, and complications. Results: A total of 197 patients were included (114 newborns in Group 1 and 83 infants in Group 2). The mean age and body weight in Group 1 were 1.2 months and 3.8 kg, respectively, whereas in Group 2, they were 3.2 months and 6.7 kg, respectively. There were no significant differences in operative time (Group 1 = 34.1 min vs. Group 2 = 32.3 min, p = 0.26), anesthetic time (Group 1 = 80.0 min vs. Group 2 = 76.3 min, p = 0.07), length of hospitalization (Group 1 = 2.3 days vs. Group 2 = 2.4 days, p = 0.88), postoperative complications including omphalitis (Group 1 = 5.3% vs. Group 2 = 1.2%, p = 0.13), wound infection (Group 1 = 0.9% vs. Group 2 = 1.2%, p = 0.81), and hydrocele (Group 1 = 0.35% vs. Group 2 = 8.4%, p = 0.14). No recurrence, testicular ascent or atrophy, or mortality was observed in either group during the 2-year follow-up period. Conclusions: Single-incision laparoscopic herniorrhaphy is a safe and effective operation for inguinal hernia repair in infants, even those with prematurity, lower body weight at the time of surgery, or cardiac and/or pulmonary comorbidities. Comparable results revealed no significant differences in perioperative complications despite younger ages and lower body weights.